Analysis of fracture data from notched specimens can provide information on multiscale toughening mechanisms. (October 2020) - Taylor, David
Graphical abstract: Highlights: Theoretical models were developed to investigate toughening mechanisms. Materials having two toughening mechanisms at different scales were studied. Distinctive features were found in notch root radius dependence. The same features were detected in experimental data from the literature. Analysis using the Theory of Critical Distances can identify the scales at which the mechanisms operate. Abstract: The identification and quantification of toughening mechanisms in materials is a difficult task which is often made more difficult by the presence of several mechanisms operating at different scales. The hypothesis behind the present work was that the length scales at which these mechanisms operate might be deduced by analysing data from fracture tests conducted on samples containing notches of different root radii. A two stage approach was adopted. Firstly, theoretical models were created using imaginary model materials with well-known toughening mechanisms. In those models having toughening mechanisms on two different scales (known as Dual materials) it was found that the larger-scale mechanism controlled the measured fracture toughness ( K cm ) for cracks and sharp notches, whilst the smaller-scale mechanism controlled the behaviour of blunter notches. This change in control created a distinct "kink" in the curve of K cm as a function of notch root radius. Secondly, experimental data from the literature were examined. Similar kinks were found to be present in the results for some materials, implying Dual behaviour. A method of prediction known as the Theory of Critical Distances (TCD) was applied to the data to estimate the relevant length scales, which in some cases coincided with those of well-known toughening mechanisms. This type of analysis may prove useful for identifying the scale, and relative importance, of toughening mechanisms in a wide variety of materials. It also provides a more accurate way to use the TCD approach to predict the effect of cracks and notches when more than one toughening mechanism is present.